The use of resazurin as a novel antimicrobial agent against Francisella tularensis - Schmitt, Deanna M.; O'Dee, Dawn M.; Cowan, Brianna N.; Birch, James W.; Mazzella, Leanne K.; Nau, Gerard J.; Horzempa, Joseph (Frontiers in Cellular and Infection Microbiology, 2013)
The highly infectious and deadly pathogen, Francisella tularensis, is classified by the CDC as a Category A bioterrorism agent. Inhalation of a single bacterium results in an acute pneumonia with a 30–60% mortality rate without treatment. Due to the prevalence of antibiotic resistance, there is a strong need for new types of antibacterial drugs. Resazurin is commonly used to measure bacterial and eukaryotic cell viability through its reduction to the fluorescent product resorufin. When tested on various bacterial taxa at the recommended concentration of 44 μM, a potent bactericidal effect was observed against various Francisella and Neisseria species, including the human pathogens type A F. tularensis (Schu S4) and N. gonorrhoeae. As low as 4.4 μM resazurin was sufficient for a 10-fold reduction in F. tularensis growth. In broth culture, resazurin was reduced to resorufin by F. tularensis. Resorufin also suppressed the growth of F. tularensis suggesting that this compound is the biologically active form responsible for decreasing the viability of F. tularensis LVS bacteria. Replication of F. tularensis in primary human macrophages and non-phagocytic cells was abolished following treatment with 44 μM resazurin indicating this compound could be an effective therapy for tularemia in vivo.